Pericapsular nerve group block for hip fracture is feasible, safe and effective in the emergency department: A prospective observational comparative cohort study. (14th June 2022) - Fahey, Alan; Cripps, Elinor; Ng, Aloysius; Sweeny, Amy; Snelling, Peter J
Abstract: Objectives: The pericapsular nerve group (PENG) block was first described for analgesia of hip fracture in 2018. We hypothesised that the PENG block is safe and effective for patients with hip fracture when provided by emergency physicians and trainees in the ED. Methods: This was an observational study of routine care. Consecutive patients receiving regional anaesthesia for hip fracture at a single ED were prospectively enrolled. Pain scores were assessed prior to regional anaesthesia then at 15, 30 and 60 min after administration. Maximal reduction in pain scores within 60 min were assessed using the Visual Analogue Scale (at rest and on movement) or the Pain Assessment IN Advanced Dementia tool (at rest). Patients were followed for opioid use for 12 h after regional anaesthesia and adverse events over the duration of admission. Results: There were 67 eligible patients during the enrolment period, with 52 (78%) prospectively enrolled. Thirty‐three received femoral blocks (19 fascia iliaca compartment blocks, 14 femoral nerve blocks) and 19 received a PENG block. Inexperienced providers were able to successfully perform the PENG block. There was no difference in maximum pain score reduction between the groups. There was no difference in adverse effects between groups. Opioid use was similar between the groups. More patients were opioid‐free after a PENG block. Conclusions: The present study demonstrated that the PENG block can be provided safely and effectively to patients with hip fracture in the ED. On the basis of this pilot study, a larger randomised controlled study should now be designed. Abstract : The PENG block is a recently described regional anaesthetic technique for analgesia of hip fractures and hip surgery. This pilot study compares the PENG block to femoral nerve block and fascia iliaca block for patients with hip fracture in the ED. The PENG block is feasible, safe and effective when performed by emergency physicians.